PENGARUH PEMBERIAN ASI EKSKLUSIF TERHADAP BERAT BADAN BAYI USIA 4-6 BULAN DI WILAYAH KERJA PUSKESMAS LANGSA KOTA - Diza Fathamira Hamzah (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2018)
ABSTRACT Exclusively breastfeeding is a best way to achieve an optimal infant growth. In practice, the exclusively breastfeeding coverage still does not reach the targets. Majority the mothers give the complementary food of breast milk to their babies under 6 month with specific reasons. It certainly affects to the baby nutritional status which can be seen from their weight gain in every month. Methods: The research used an analitic method with case study design which aims to know the affect of exclusively breastfeeding on infants’ weight age 4 to 6 months in Langsa Kota Community health center’s region. The population were 82 babies in October till December 2017 and 68 of them were used as the study sample obtained by simple random sampling. The data were collected by using weighing babies’ weight data from Posyandu and questionnaires. The affect of exclusively breastfeeding on weight of infant age 4 to 6 months analysed by independent T Test with confident level 95%. Result: The result showed that the exclusively breastfeeding significantly affected to the infants’ weight age 4 to 6 month (p value 0,000). Conclusion: It is recommended for all health workers in Langsa Kota Community health center’s region to improve the community awareness about exclusively breastfeeding present for their babies from newborn till 6 months. Keywords: exclusively breastfeeding, weight gain